SUBJECTIVE EVALUATION OF COMMUNICATION AT PATIENS AFTER TOTAL LARYNGECTOMY - Kučerová, Jana (Profese Online, 2009)
The article shows results of survey, that was focus on finding psychological, social and biological factors and subjective satisfaction with voice before and after total laryngectomy of patients with carcinoma of larynx. The biggest problem for patients after total laryngectomy is loss communication. More than half patients acquire voice compensatory voice with big bothers.
Keywords: carcinoma of larynx; total laryngectomy; psychological; social and biological factors; subjective satisfaction with voice